PERANAN APLIKASI BJB DIGI DALAM MENINGKATKAN MINAT PEMBUKAAN REKENING TABUGAN BAGI MAHASISWA PERBANKAN DAN KEUANGAN DIPLOMA FEB UPNVJ - Alia Putri Lestari (2021)
In carrying out it is business activities, bank have one form of saving, namely savings account. Savings acaount is a form of savings that can be used at any time without a time period for making withdrawals. The opening of savings accounts at this time has varied, it can be done coming to the bank or online. This can happen because of the encouragement of technological developments in the banking world. For bank Bjb, account opening can be done through the bjb DIGI application, you only need to complete personal data as a condition for opening an account through the bjb DIGI application on a smartphone, such as photos of front and back ID cards, selfie photos holding ID cards, and email. bjb DIGI is basically an application that contains a report on changes in equity (LPE) contained on a smartphone which includes a menu of Bjb sms, Bjb net, bank Bjb mobile banking and other bank products according to the bank's business needs. Or it can be said as a facility, an electronic-based banking service issued by bank Bjb to make it easier for customers to make transactions in a safe, comfortable and fast manner, because it can be accessed anytime using a Smartphone. bjb DIGI can be said as mobile banking for bank Bjb.